2006
DOI: 10.1177/0191453706061090
|View full text |Cite
|
Sign up to set email alerts
|

Intersubjectivity – interactionist or discursive? Reflections on Habermas’ critique of Brandom

Abstract: This article argues that there is a marked ambivalence in Habermas' concept of intersubjectivity in that he wavers between an interactionist and a discursive understanding. This ambivalence is demonstrated with reference to his recent critique of Robert Brandom's normative pragmatic theory of discursive practice. Although Habermas is a leading theorist of discourse as an epistemically steered process, he allows his interpretation of Brandom's theory as suffering from objective idealism to compel him to recoil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(18 reference statements)
0
3
0
2
Order By: Relevance
“…The latter includes negotiated assent consisting of linguistically mediated interaction between individuals, ultimately oriented toward mutual understanding [75]. Specifically, Habermas critiques the notion that individuals can reach a fixed solution applicable to all when societal situations are constantly changing; and challenges how individuals can reach universal conclusions in isolation and separation from their context [76]. Analysis of workplace bullying and leadership paradigms in the context of NPM-oriented radical alterations to UK public sector structures, culture, and practices remains limited.…”
Section: Annals Of Social Sciences and Management Studiesmentioning
confidence: 99%
“…The latter includes negotiated assent consisting of linguistically mediated interaction between individuals, ultimately oriented toward mutual understanding [75]. Specifically, Habermas critiques the notion that individuals can reach a fixed solution applicable to all when societal situations are constantly changing; and challenges how individuals can reach universal conclusions in isolation and separation from their context [76]. Analysis of workplace bullying and leadership paradigms in the context of NPM-oriented radical alterations to UK public sector structures, culture, and practices remains limited.…”
Section: Annals Of Social Sciences and Management Studiesmentioning
confidence: 99%
“…Habermas critique Brandom en se plaçant du point de vue de l'interaction, c'est-à-dire du point de vue d'une théorie du dialogue. Plutôt que d'adopter une position intersubjectiviste discursive, il avance un intersubjectivisme dialogique et interactionniste (Strydom, 2006) se concentrant sur la stricte relation entre une première et une seconde personne. D'un côté, une première personne est un locuteur qui associe une intention à un acte de discours et qui, comme interlocuteur, adresse cette assertion à un destinataire en lui demandant de répondre publiquement par l'affirmative ou par la négative.…”
Section: Objections Et Réponse De Habermasunclassified
“… 4 Piet Strydom (2006) soutient ce point, mais il s'en tient à une analyse critique de la position de Habermas, alors que nous visons ici à répondre à cette critique en explicitant la spécificité du processus discursif théorisé par Brandom.…”
unclassified
See 1 more Smart Citation
“…15. Elsewhere (Strydom, 2006), I have shown that the model of mutual understanding based on social interaction is too limited; the discursive model going beyond double contingency to the full threefold structure of communication which includes the third point of view must also be considered. 16.…”
Section: Notesmentioning
confidence: 99%